Interactive Gene Expression Patterns of Susceptible and Resistant Lens ervoides Recombinant Inbred Lines and the Necrotroph Ascochyta lentis - Cao, Zhe; Kapoor, Karan; Li, Li; Banniza, Sabine (Frontiers in Microbiology, 2020)
Ascochyta lentis is a foliar pathogen of Lens species and is of worldwide importance in cultivated lentil production. High levels of resistance were identified in the wild species Lens ervoides. This resistance was explored through histopathology, qPCR estimation of fungal biomass and transcriptome sequencing in a susceptible and a resistant recombinant inbred line (RIL) of L. ervoides infected with an aggressive isolate of A. lentis. Necrotrophic growth was delayed in the resistant RIL compared to accelerated necrotrophy of A. lentis in the susceptible RIL. Analysis of the fungal secretome indicated that the early activation of cell wall-degrading enzymes contributed to increased virulence of A. lentis. On the host side, gene co-expression analysis revealed that the invasion by A. lentis caused mRNA, DNA and protein decay in infected plants regardless of the level of resistance in the host. The resistant RIL exhibited a stronger co-gene expression in lipid localization and sulfur processes, and cellular responses to nutrients and stimuli than the susceptible RIL. In addition, differential gene analysis revealed that the repression of both, gibberellin signaling and cell death associated with the hypersensitive response (HR), were associated with enhanced A. lentis resistance.